Gender dan Performansi Kognitif (Book Review) - Andayani, Andayani (Sunan Kalijaga State Islamic University & The Asia Foundation, 2008)
Judul Buku : Gender Differences in Human CognitionPenulis : Paula J. Kaplan, Mary Crawford, Janet Shibley Hyde dan John TE RichardsonPenerbit : Oxford Â University Â PressTahun : 1997Tebal : 182 Halaman